Modelling Lake Volumes and Runoff on the Western Greenland Ice Sheet - Lund, Sarah (The University of Edinburgh, 2011)
Supra-glacial lakes can act as a key regulator of variable surface meltwater to the ice-bed interface on the Greenland Ice Sheet. In light of recent numerical studies focussing on the impact of variable surface meltwater inputs to ice sheet dynamics this study looks at the role surface melt water generation and routing has on the formation and growth of supra-glacial lakes using a modelling and spatial analytical approach. Results are validated with high temporal resolution MODIS imagery and suggest a relationship between the spatial location of lakes on a computed flow accumulation drainage network and their timing of formation, growth rate and drainage. Lakes which are positioned at the top of their drainage catchments initiate during the transition period from snow to ice and grow at a rate proportional to the surrounding snow and ice melt. Lakes which fall on the network further ‘downstream’ display complicated patterns of secondary growth and drainage linked to reductions in volume of larger lakes ‘upstream’ suggesting these lakes capture surface overflow from larger supra-glacial lakes before any full drainage beneath the ice.